Dinâmica do escoamento superficial e da erosão em encostas sob plantio direto - Londero, Ana Lúcia (2019)
No-till (NT) is adopted worldwide. In Brazil, it covers more than 32 million hectares and is used as a strategy for soil conservation. However, research led in South Brazil, a region which stands out in NT agricultural production, show erosion problems in its results, highlighting that the current land management, soybeans/wheat or oats binomial, simplifies NT’s principles and favors surface runoff. Therefore, this study evaluates the hydrological and erosive behavior of agricultural hillslopes under NT and different water, soil and plant management conditions. The study took place at the Seeds Research Center, in Júlio de Castilhos, where the soil is classified as a Nitisol. Six monitoring units were exploited: two zero-order catchments (2.4 ha) of convergent curvature and four rectilinear macroplots (0.6 ha). Water and soil losses were measured at monitoring sections installed on the outlet of each hillslope, under natural rainfall condition. As water management, the use of terraces was tested (with and without terraces), while scarification and crop rotation were tested as soil and plant managements. Monitoring occurred between 2014 and 2018, with a total of 63 monitored events in the catchments and 27 in the macroplots. The results demonstrate that used NT is not enough to control runoff and erosive processes. The introduction of water management reduced water losses in 56% and 70% of soil losses. The adoption of water management reduced water loss in 56% and soil loss in 70%. Plant management pronouncing greater phytomass addition was not efficient in controlling runoff for medium and high magnitude events, but it was efficient in controlling soil losses. Soil management (scarification) only reduced water losses when compared to planting with low addition of phytomass, and is not a recommended management. The hydraulic parameters were estimated and presented considering the magnitude of the rainfall and cover seasonality, reinforcing the benefits of the adoption of terracing and the influence of the relief in runoff propagation. This demonstrated the importance of monitoring studies on paired hillslope and catchment scales, in order to understand the hydrological and sedimentological behavior of different water, soil and plant management practices associated with no-tillage and the determination of more conservationist strategies for agricultural development.